THE INFLUENCE OF ISLAMIC LEADERSHIP AND ISLAMIC WORK ETHICS ON EMPLOYEE PERFORMANCE OF ISLAMIC BANKS IN RIAU PROVINCE MEDIATED BY ISLAMIC ORGANIZATIONAL CULTURE - Hamzah, Zulfadli; Basri, Yuswar Zainal; ., Zulhelmy (International Journal of Islamic Business & Management, 2021)
The purpose of this research is to examine the effect of Islamic leadership and Islamic work ethics on employee performance of Islamic banks in Riau province, whereby Islamic organizational culture became the mediator variable. This research employs the Structure Equation Model (SEM) based on Partial Least Square (PLS) with the help of SmartPLS 3.0 M3 software. The data were collected by using a questionnaire from 275 respondents. The respondent in this research was an employee of Islamic banks in Riau Province. The result showed that Islamic leadership, Islamic work ethics, and Islamic organizational culture positively and significantly influence on employee performance of Islamic banks in Riau province. On another side, the Islamic leadership mediated by Islamic organizational culture does not significantly influence on employee performance of Islamic Banks in Riau Provence. The finding of this research suggests that to enhance the role of Islamic leadership to create Islamic organization culture and Islamic work ethics increasingly would be an effect on employee performance of Islamic Bank in Riau province.JEL Classification Codes : M1, G21, M540.